2022
DOI: 10.1002/1878-0261.13274
|View full text |Cite
|
Sign up to set email alerts
|

FGF7/FGFR2JunB signalling counteracts the effect of progesterone in luminal breast cancer

Abstract: We have recently demonstrated that fibroblast growth factor receptor 2 (FGFR2)‐mediated signalling alters progesterone receptor (PR) activity and response of oestrogen receptor α (ER)‐positive (ER+) breast cancer (BCa) cell lines to anti‐ER agents. Little is known about whether the crosstalk between ER and PR, shown to be modulated by the hormonal background, might also be affected by FGFR2. Here, PR‐dependent behaviour of ER+ BCa cells was studied in the presence of oestrogen (E2) and progesterone (P4) and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 88 publications
(100 reference statements)
2
11
0
Order By: Relevance
“…Additionally, correlation analyses of the high- vs. low-risk healthy patients were in line with other previously published data showing that uncontrolled ECM remodelling and reorganization are characteristic for high-risk breast tissue [ 58 , 59 ]. This is particularly interesting in light of recent studies focused on context-dependent prognostic significance of FGFR2 in invasive BCa [ 23 , 24 ] and identification of highly oncogenic truncated FGFR2 variant [ 60 ]. Since clinical responses to various FGFR2 inhibitors among BCa patients have still remained highly variable, there is the need to identify and better understand co-regulators of FGFR2-dependent cellular functions at the different stages of disease progression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, correlation analyses of the high- vs. low-risk healthy patients were in line with other previously published data showing that uncontrolled ECM remodelling and reorganization are characteristic for high-risk breast tissue [ 58 , 59 ]. This is particularly interesting in light of recent studies focused on context-dependent prognostic significance of FGFR2 in invasive BCa [ 23 , 24 ] and identification of highly oncogenic truncated FGFR2 variant [ 60 ]. Since clinical responses to various FGFR2 inhibitors among BCa patients have still remained highly variable, there is the need to identify and better understand co-regulators of FGFR2-dependent cellular functions at the different stages of disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…HB2 cells with stable knock-down of FGFR2 were established with shRNA-based lentiviral construct as previously described [ 24 , 27 ]. HB2 FGFR2(-) cells were maintained in a medium supplemented with 0.2 µg/ml puromycin (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In silico gene expression analysis was performed by utilizing data of the METABRIC cohort, publicly available from cBioPortal™ for Cancer Genomics (Breast Cancer, METABRIC dataset) [ 37 , 38 ], as previously described [ 8 ]. mRNA levels of FGFR2 and NFE2L2 were determined using the expression microarray method and available clinicopathological characteristic was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…We have also showed that the significance of FGFR2 in ER+/PR+ BCa patients depends on their menopausal status. The good prognostic effect of high expression of FGFR2 was lost in premenopausal BCa patients [ 8 ].…”
Section: Introductionmentioning
confidence: 99%